Advances in Internal Combustion Engine Research (Energy, Environment, and Sustainability,, 2018)
This book discusses all aspects of advanced engine technologies, and describes the role of alternative fuels and solution-based modeling studies in meeting the increasingly higher standards of the automotive industry. By promoting research into more efficient and environment-friendly combustion technologies, it helps enable researchers to develop higher-power engines with lower fuel consumption, emissions, and noise levels. Over the course of 12 chapters, it covers research in areas such as homogeneous charge compression ignition (HCCI) combustion and control strategies, the use of alternative fuels and additives in combination with new combustion technology and novel approaches to recover the pumping loss in the spark ignition engine. The book will serve as a valuable resource for academic researchers and professional automotive engineers alike.